Television advertising to young children - T. Cardwell-Gardner Cardwell-Gardner; J.A. Bennett (Communicare)
Children are becoming increasingly important as a focus for marketing strategies as a result of not only their increased purchasing power, but also because of the influence they exert on parental purchasing decisions. Currently, little is known about how children view television advertising messages directed at them, or the advertising formats that appeal to them. The purpose of this research was therefore to discover how young children view television adverts directed specifically at them. Data was collected by making use of eight focus groups. The findings suggest inter alia that separate messages must be formulated for boys and girls, that messages must contain a cleverly told story, and that the message must be relevant to them